Students Perception about Learning Strategies in Reading English Text - Samuel Kubela; Stella Rose Que; Jusak Patty (MATAI: International Journal of Language Education, 2022)
Reading is an essential skill for learners in order to ensure their success not only in learning English, but also in learning in any content class. This study aimed at identifying types of students’ reading strategies, challenges during the implementation of those strategies and solutions in maximizing the implementation those strategies. This study was a survey research conducted at SMA Katolik Yos Sudarso Dobo. The data were collected by using questionnaire, which was distributed to the respondents consisting of 60 students and were analyzed by using descriptive statistic. The result of the study showed that: 1) 34 students or 56,70% strongly agree that efficiency of silent reading strategies was the most dominant reading strategy used by them; 2) 40 students or 66,7% strongly agree that they find it difficult to understand the sentence in the English text; 3) 34 students or 56,70% strongly agree that they think about the information that is in the text into Indonesian when reading. The results of the study above reveals that reading proficiency plays a great role in understanding a written statement accurately and efficiency. Therefore, teachers should provide students with several of reading strategies that can help them to comprehend the text.